2020
DOI: 10.1002/er.5416
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of GO to rGO due to 8.0 MeV carbon (C++) ions irradiation and characteristics performance on MnO 2 –NiO–ZnO @ GO electrode

Abstract: Summary The effect of 8.0 MeV carbon ions (C++) radiations on features and performances of MnO2–NiO–ZnO@GO electrodes (thin films). MnO2–NiO–ZnO@GO thin films were produced using the hydrothermal technique. 8.0 MeV carbon ions (C++) with doses of 2.25 × 1015, 5.0 × 1015, 7.5 × 1015 and 1.0 × 1016 ions/cm2 were irradiated on MnO2–NiO–ZnO@GO thin films. The XRD spectra indicate crystalline nature of the films while SEM images show rod‐like structures. The XRD calculated crystallite sizes varied from 1.24 to 5.58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Graphene is a sheet of refined graphite in which the atoms are densely and closely packed. These graphite atoms that formed graphene are arranged systematically and neatly hexagonal configuration [37,41]. Their unique features like great specific surface area, good electrical conductivity and established chemical reaction (inertness) make them a good candidate for energy storage devices.…”
Section: Graphene Materials In Lisbsmentioning
confidence: 99%
“…Graphene is a sheet of refined graphite in which the atoms are densely and closely packed. These graphite atoms that formed graphene are arranged systematically and neatly hexagonal configuration [37,41]. Their unique features like great specific surface area, good electrical conductivity and established chemical reaction (inertness) make them a good candidate for energy storage devices.…”
Section: Graphene Materials In Lisbsmentioning
confidence: 99%
“…The pressing demand for energy arises as a direct consequence of continuous global population growth, creating a palpable energy deficit in numerous nations across the globe [1][2][3]. To mitigate this shortfall, researchers have pioneered the development of energy storage devices, with supercapacitors (SCs) emerging as a particularly intriguing technology owing to their significant attributes such as high energy density and prolonged lifespan [4][5][6][7]. Notably surpassing the energy density of conventional capacitors, SCs represent a promising technological advancement that addresses the escalating energy requisites of storage systems [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that composite materials perform better compared to their individual components because of the synergetic effect among the combined components [25,26]. Ramesh et al [27] worked on hierarchical flowerlike 3D nanostructure of Co 3 O 4 @MnO 2 /N-doped Graphene oxide (NGO) hybrid composite for a high-performance supercapacitor.…”
Section: Introductionmentioning
confidence: 99%